Students’ Reluctance on Attending the Webinar Tutorial (Tuweb) of Speaking Course: A Case Study at Universitas Terbuka - Siti Hadianti (Faculty of Letters Universitas Balikpapan, 2023)
It can be difficult to motivate students to attend classes while using a digital platform for instruction. Students at Universitas Terbuka who have registered for the Speaking course's online tutorial program are required to attend every session of the webinar tutorial (Tuweb) synchronously. However, the tutors' evaluations revealed that the student's attendance in these real-time classes was not optimum. This study aims to investigate the problem by looking at the reasons why students find it difficult to enroll in the Speaking course synchronously. A qualitative case study using type 2 design where the researcher compared each online class to another. Participants in this study are tutors from sixteen Tuweb courses. The author divided the class into two sections based on the attendance rates, with the highest and lowest divisions being used for comparison. Based on the analysis of data, it is found that there were at least two kinds of problems in Tuweb which the author labeled as generalized external constraint and personalized internal constraint. The researcher also found that two reasons can affect the students' reluctance level in Tuweb class, the first is the personal approach and the second one is the non-personal approach.